Two views on a single research object: mixed language code - Шумарова, Наталія Петрівна (Київський національний університет імені Тараса Шевченка, 2024)
The purpose of this article was to present the approaches and methods of Ukrainian and European scientists to the research of the interaction of two languages – Ukrainian and Russian in the communication processes between different segments of the society. As a result of close contacts, a mixed code with an uncertain status emerged, which received the figurative name “surzhyk” and was assessed by Ukrainian sociolinguistics as a threat to the development and functioning of the Ukrainian, primarily literary, language. The goal of the study was to analyze how the research object is presented in European science, namely in a scientific project in which Austrian, German and Ukrainian researchers participated (2019 – 2024). The research content was articles on mixed code published in Ukraine and abroad, as well as reports delivered at the seminar “Hybridization from two sides: Ukrainian-Russian and Russian-Ukrainian Code Mixing in the context of the (socio)linguistic situation in southern Ukraine along the Black Sea coast”, which took place in February 2024 in the Alpine-Austrian. University (Klagenfurt, Austria) and the participants of the project with the same name - researchers from the above-mentioned University named after Karl von Ossetsky (Institute of Slavic Studies), as well as Ukrainian and Polish researchers. This article belongs to the comparative and general research, therefore, the methods with which the author worked include the comparative method and the method of induction, which enabled to identify certain trends in the development of scientific thought in specific cases. The methods of analysis and synthesis allowed to analyze the approaches and methods of studying the results of the language mixing, which is Ukrainian-Russian Surzhyk. The analysis of the approaches and methods of analysis, recorded in the works of Ukrainian and Western European scholars - project participants, allowed us to draw conclusions that, when studying surzhyk, researchers have different goals in front of themselves. Ukrainian sociolinguists present it as a negative consequence of the existence of bilingualism on the territory of Ukraine, as a threat to the functioning and development of the Ukrainian language, as a space of interference phenomena in the structure of expressions. German and Austrian participants of the project, considering the historical and cultural development of Ukraine, consider surzhyk as a code that arose as a result of the complex communication interaction of languages and dialects living on the Ukraine’s territory, look for nodes of stabilization in it, single out regional lexifiers that form this code, analyze the systematic signs of the code due to the reduction of the variability of its units. Both groups emphasized the need to regard dialectal influences that allow to discuss different types of surzhyk, consider surzhyk a language of limited use and do not predict its establishing as a third language that ensures communication in society.

Метою цієї статті є представлення підходів і методів українських та європейських учених до вивчення взаємодії двох мов - української та російської у процесах комунікації різних верств населення. У результаті тісних контактів виник змішаний код із невизначеним статусом, що отримав образну назву «суржик» і оцінювався українською соціолінгвістикою як загроза розвитку і функціонуванню української, насамперед літературної, мови. Завданням роботи є аналіз того, як презентовано об’єкт дослідження в європейській науці, а саме в науковому проєкті, в якому брали участь австрійські, німецькі та українські дослідники (2019-2024). Матеріалом дослідження стали статті про змішаний код, опубліковані в Україні та за кордоном, а також доповіді, виголошені на семінарі «Гібридизація з двох боків: українсько-російське та російсько-українське кодове змішування в контексті (соціо)лінгвальної ситуації на півдні України вздовж узбережжя Чорного моря» («Hybridization from two sides: Ukrainian-Russian and Russian-Ukrainian Code Mixing in the context of the (socio)linguistic situation in southern Ukraine along the Black Sea coast», який відбувся в лютому 2024 р. в Альпійсько-австрійському .університеті (м. Клагенфурт, Австрія) і на якому виступили учасники однойменного проєкту - дослідники з названого вище університету, Університету ім. Карла фон Оссецького (Інститут славістики), м. Ольденбурга, (Німеччина), а також експерти з України і Польщі. Методи дослідження. Ця стаття належить до праць порівняльного і узагальнювального плану, тому до методів, з якими працював автор, належать зіставно-порівняльний метод і метод індукції, який дозволив за конкретними випадками побачити певні тенденції в розвитку наукової думки. Методи аналізу і синтезу дозволили проаналізувати підходи й методику вивчення результатів змішування мов, яким є українсько-російський суржик. Аналіз підходів, методів аналізу, зафіксованих у працях українських і західноєвропейських учених – учасників проєкту, дозволяє зробити висновки, що, вивчаючи суржик, дослідники ставлять перед собою різну мету. Українські соціолінгвісти презентують його як негативний наслідок існування двомовності на території України, як загрозу функціонуванню й розвитку української мови, як простір інтерферентних явищ у структурі висловлень. Німецькі й австрійські учасники проєкту, зважаючи на історичний і культурний розвиток України, розглядають суржик як код, що виник у результаті складної комунікаційної взаємодії мов і діалектів, що побутують на території держави, шукають в ньому вузли стабілізації, виокремлюють регіональні лексифікатори, які формують цей код, аналізують ознаки системності коду через зменшення варіативності його одиниць. Обидві групи підкреслюють необхідність врахування діалектних впливів, які дозволяють говорити про різні види суржику, вважають суржик мовою обмеженого вживання і не прогнозують його усталення у вигляді третьої мови, що забезпечує комунікацію соціуму.
Keywords: mixed code; surzhyk; variability; stabilization; communication; комунікація; змішаний код; суржик; варіативність; стабілізація